Demonstration Method and Students’ Practical Skill Development in Islamic Funeral Management: A Qualitative Study - Oki Asra Said; M. Yemmardotillah (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the implementation of the demonstration method in enhancing students’ practical skills in Islamic funeral management, to analyze students’ responses toward its application, and to identify the supporting and inhibiting factors influencing its effectiveness in Islamic Religious Education. Although demonstration-based learning has been widely discussed in previous studies, research specifically addressing its comprehensive application in fiqh al-janāzah remains limited. This study employed a qualitative approach with a case study design, involving 30 participants selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. To ensure data validity, triangulation and member checking were applied. The findings reveal that the demonstration method significantly improves students’ practical skills across cognitive, affective, and psychomotor domains. The method facilitates experiential learning by enabling students to directly observe and practice procedural stages, thereby enhancing understanding, engagement, and skill accuracy. Students demonstrated positive responses, including increased motivation, active participation, and deeper conceptual comprehension. However, the effectiveness of the method is influenced by several factors, including teacher competence, availability of learning resources, student readiness, time constraints, and psychological aspects. The novelty of this study lies in its holistic analysis of demonstration-based learning in Islamic funeral management, covering all procedural stages while integrating students’ responses and contextual factors. Unlike previous studies that focus primarily on cognitive outcomes or partial aspects of religious practices, this research highlights the integration of cognitive, affective, and psychomotor domains within a constructivist and experiential learning framework in a religious education context. This study contributes theoretically by strengthening constructivist and experiential learning perspectives in Islamic Religious Education and expanding their application to practice-based religious learning. Practically, it provides insights for educators in designing interactive, structured, and practice-oriented instructional strategies that enhance students’ engagement and skills. The findings also offer implications for curriculum development and encourage further research on innovative and adaptive learning models in religious education.